1984
DOI: 10.1017/s0022172400064536
|View full text |Cite
|
Sign up to set email alerts
|

Antibody against viruses in maternal and cord sera: non-specific inhibitors are found to higher titre on the maternal side of the circulation

Abstract: SUMMARYPregnancies were identified in which maternal IgG antibodies against rubella virus were not detectable by single radial haemolysis. Twenty paired maternal/cord sera were then tested for haemagglutination-inhibiting (HI) activity against rubella virus without kaolin pretreatment of the sera. In the absence of specific antibody, the HI activity observed could thus be ascribed to the effect ofnon-specific inhibitors. The HI activity in maternal sera was significantly (P < 0 001) higher than that in cord se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Higher maternal levels of antibody were found for rubella, HIV and Plasmodium falciparum. 15,26,27 All of these data suggest that the transplacental transfer of antibody from mother to infant is selective. 28 Previous studies of maternal-infant IgG subclasses to various pathogens demonstrated higher levels of IgG1, lower levels of IgG2, and equivalent levels of IgG3 and IgG4 in maternal sera compared with that of their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Higher maternal levels of antibody were found for rubella, HIV and Plasmodium falciparum. 15,26,27 All of these data suggest that the transplacental transfer of antibody from mother to infant is selective. 28 Previous studies of maternal-infant IgG subclasses to various pathogens demonstrated higher levels of IgG1, lower levels of IgG2, and equivalent levels of IgG3 and IgG4 in maternal sera compared with that of their infants.…”
Section: Discussionmentioning
confidence: 99%